Product Photography of Uniqlo Indonesia As A Promotion Medium On Instagram Social Media - Prasetyo, Martinus Eko; Budiargo, Kresnawan (Universitas Ciputra, 2024)
This research discusses the role of product photography in the UNIQLO Indonesia brand as a promotional medium on the Instagram social media platform, where social media is one of the most important tools for brand promotion activities. With the rapid growth of Instagram users in Indonesia, UNIQLO has successfully utilized visual and narrative strengths to build a strong brand image, communicate brand values, and increase awareness and consumer interest in its products. This research analyzes how UNIQLO uses product photography to capture the essence of its unique collections, showcase functional designs, and convey brand messages. The study is conducted qualitatively with a case study on Instagram posts on the UNIQLO Indonesia account. Through this exploration, insights are gained into product photography techniques, shooting angles, display, and lighting techniques. The research highlights the importance of product photography in the activities of the UNIQLO brand, as evidenced by storytelling, brand images and aesthetic impressions, user engagement, promotion, and sales.